2007
DOI: 10.2353/ajpath.2007.060828
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Oligosaccharides Inhibit Tumorigenicity of Osteosarcoma Cell Lines MG-63 and LM-8 in Vitro and in Vivo via Perturbation of Hyaluronan-Rich Pericellular Matrix of the Cells

Abstract: Numerous studies have demonstrated a correlation between hyaluronan expression and the malignant properties of various kinds of cancer, and inhibition of hyaluronan production causes decreased tumor growth. Hyaluronan oligosaccharides have been shown to inhibit several tumor cell types via disruption of receptor-hyaluronan interaction. However, few studies have addressed hyaluronan with respect to osteosarcoma. In this study, we examined the effects of exogenously added hyaluronan oligosaccharides on tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…Motility and the invasive nature of osteosarcoma cells are abolished by the same treatment [9], which suggests an involvement of the PCM in cancer cell metastasis. Endothelial cells lose their ability to respond to fluid flow when HA is enzymatically removed [7].…”
Section: Introductionmentioning
confidence: 85%
“…Motility and the invasive nature of osteosarcoma cells are abolished by the same treatment [9], which suggests an involvement of the PCM in cancer cell metastasis. Endothelial cells lose their ability to respond to fluid flow when HA is enzymatically removed [7].…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies on chondrocytes and tumor cells had demonstrated that an effective concentration of 250 mg/ml of exogenous HA oligos was necessary to affect cell behavior. 20,26 The cells were cultured in the presence or absence of various-sized of 250 mg/ml HA oligos or HMWHA in chamber slides at a concentration of 2 Â HA Oligosaccharides HA oligos; tetrasaccharides (HA4), hexasaccharides (HA6), octasaccharides (HA8), decasaccharides (HA 10), and dodecasaccharides (HA12), were prepared by Seikagaku Co. as described previously. 27 The purity and size of each HA oligos were confirmed using high performance liquid chromatography analyses.…”
Section: Cell Culturementioning
confidence: 99%
“…In these studies, an oligosaccharide length of more than octasaccharides was required for these effects. 20 A recent report showed HA-CD44 interaction plays an important role in the property of highly tumorigenic ovarian carcinoma cells and HA oligo is one of the therapeutic candidates to abrogate the properties of these cells. 21 However, no studies have ever investigated the effects of HA oligos on bone metastasis associated with several solid tumors/carcinomas.…”
mentioning
confidence: 99%
“…These oligosaccharides are most likely generated by digestion with Chnase in vivo because their reducing terminal sugar residues are GalNAc. Note that HA oligosaccharides liberated by digestion with hyaluronidases have biological activities, such as induction of the transcription of metalloproteases (37), enhancement of tumor cell motility (38), and inhibition of the tumorigenicity of cancer cells (39). A disaccharide derived from CS was also demonstrated to promote recovery of the central nervous system by modulating both neuronal and microglial behavior (40).…”
mentioning
confidence: 99%